Review of Overlandflow Quality in Densely Settled Sub-Urban Areas - Sudarmadji, S (Forum Geografi, 1997)
The study aims to analyse quality of water from overlandflow in the sub-urban area having high of to houses, in the Sinduharjo, Sleman regency. In the sub urban area, the run off originated from paved and impermeable are which is not uniformaly distributed over the area. Run off is iniated from detention storage and overlandflow. Therefore any water pollution of the runoof begin from overlandflow which dissolves constituent within the soil and rock materials. Land cover also determines the dispersion agent of rain water thus the affect the material dissolved in the water. As an input into the catchment system, rainfall affects overlandflow, quantitative, and qualitatively. Overlandflow from open space in the sub-urban area was evaluated based on physical and chemical characteristics. Overlandflow from urban area has chemical parameters such as C, NO2, NO3, and PO4 are higher than those in overlandflow from rural area which is covered by forest and garden. Overlandflow shows BOD and COD in relatively high concentration. Overlandflow is not recomended to be discharge into infiltration wells, unless it is free from parts having high significant contamination.